2003
DOI: 10.1063/1.1527629
|View full text |Cite
|
Sign up to set email alerts
|

Ion emission from solid surfaces induced by intense electron beam impact

Abstract: Ions or ionized neutrals released from solid surfaces by electron beam impact can be accelerated and trapped in the beam potential causing beam disruption. Experiments have been performed on the DARHT-I accelerator (1.7 kA, 19.8 MeV, 60 ns) to study this phenomenon. The beam, focused to a range of diameters, was transmitted through thin targets made of various materials. The time evolution of the beam radial profile was measured downstream of the target. For low current density, the downstream-beam radial prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…This causes ion focusing or disruption of the beam [11], either of which invalidates the imaging data. The threshold for these effects is over 300 C [12]. We estimated the temperature of the target by integrating time resolved reconstructions of the beam current-density profile to produce a map of charge deposition, and then estimated the peak temperature using the stopping power and specific heat of the SiO target.…”
Section: Resultsmentioning
confidence: 99%
“…This causes ion focusing or disruption of the beam [11], either of which invalidates the imaging data. The threshold for these effects is over 300 C [12]. We estimated the temperature of the target by integrating time resolved reconstructions of the beam current-density profile to produce a map of charge deposition, and then estimated the peak temperature using the stopping power and specific heat of the SiO target.…”
Section: Resultsmentioning
confidence: 99%
“…If we ignore beam-target interactions 21,22 for the moment, then the three main contributing factors governing the spot size r at the final focus are emittance, beam transport mismatches, and spherical aberration. The scaling of r can be determined analytically by considering the root sum of the squares for each contributing factor and finding the optimum spot size in terms of the convergence angle a.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication, results of an experimental ͑using the DARHT first axis beam; 19.8 MeV, 1.7 kA, and 60 ns flattop pulse͒ and theoretical study to understand the extent of this phenomenon were reported. 7 There, the beam, focused to a range of diameters, was transmitted through thin targets made of various materials, and the time evolution of the beam radial profile was measured downstream of the target. A number of metal targets along with graphite were used.…”
Section: Introductionmentioning
confidence: 99%